Phobia and Fear of COVID-19: origins, complications and management, a narrative review - Heiat, M.; Heiat, F.; Halaji, M.; Ranjbar, R.; Tavangar Marvasti, Z.; Yaali-Jahromi, E.; Azizi, M. M.; Morteza Hosseini, S.; Badri, T. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. The outbreak of Coronavirus Disease 2019 (COVID-19) have changed into a global crisis. Psychologically, this process of alteration can lead to feelings of fear, insecurity, and anxiety. This fear and anxiety can be caused by a variety of factors. However, due to the lack of extensive studies at this time, there are little data on these conditions related to COVID-19. Therefore, in this narrative review, we have tried to identify the most important possible causes of anxiety and fear due to this disease, based on logical shreds of evidence. Then we tried to discuss the consequences and ways to manage and prevent them. Methods. The current focus was on three major axes of corona-phobia, fear and anxiety. PubMed, Science Direct, Scopus, Google Scholar and authoritative news and information sources were considered as the data sources.Results. Findings from the analysis of the results revealed that, in addition to the real and the logical reasons which belong to the intrinsic properties of SARS-CoV-2, some misleadings and misconceptions induced by media, governmental policies, public awareness level, and non-scientific speculations and contradictory data expressed by experts, researchers and scientific societies, could provide the way for the development of corona-phobia, and fear.Conclusions. Each of these causal components, in its place, leads to some degrees of psychological disorders and subsequent consequences and complications. Finally, here we reviewed, summarized the previous research findings on how to prevent and manage this type of psychological disorder, and made comparisons.